INCORPORATING DIRECTED READING THINKING ACTIVITY (DRTA) TECHNIQUE INTO EXTENSIVE READING CLASS - Rukminingsih, Rukminingsih (IAIN Ponorogo, 2014)
Abstract: This research focused on incorporating Directed Reading Thinking Activity (DRTA) technique into Extensive Reading to the Fourth semester of English Department in STKIP PGRI Jombang. This research applied a qualitative research in which observation, interview, and documentation employed as data collection techniques. The findings showed that the implementation of data can be combined by several techniques in order to develop the understanding and make the students enjoy, interest, and enthusiasm during teaching learning process.Â ÙÙ Ø¹Ø¨Ø§Ø±ÙØ§ ÙØµÙÙ ÙØ§Ø·ÙÙØ§ Ø©Ø¹Ø³Ø§Ù Ø©Ø¡Ø§Ø±ÙÙØ§ ÙÙ Ø©ÙÙÙØª )DRTA( Ø±Ø®Ø¢ ÙØ±ÙÙØªÙØ§ Ø©Ø¡Ø§Ø±ÙÙØ§ Ø¬Ø§Ø±Ø®Ø¥ Ø¬Ù Ø¯ ÙÙØ¹ Ø«ØØ¨ÙØ§ Ø§Ø°Ù Ø²ÙØ±Â ØØ©Ø¸ØÙØ§ÙÙ Ø§ ÙØ°ÙØ§ ÙØ¹ÙÙÙØ§ Ø«ØØ¨ÙØ§ ÙÙ ÙÙÙØ¨Ø·ØªÙØ§ Ø«ØØ¨ÙØ§ Ø§Ø°Ù .STKIP PGRI Jombang ÙÙ Ø©ÙØ²ÙÙÙØ¬ÙØ¥Ø§ Ø©ØºÙÙØ§ Ù Ø³ÙÂ ÙÙØ¨ Ø¹Ù ÙØ¬Ø§ ÙÙÙÙ DRTA Ø°ÙÙÙØª ÙØ£ Ø¬Ø¦Ø§ØªÙÙØ§ ØªØ±ÙØ¸Ø£Ù .ØªØ§ÙØ§ÙØ¨ÙØ§ Ø¹Ø¬Ù ØªØ§ÙÙÙØª ÙØ¹ Ø©Ù Ø¯Ø®ØªØ³ÙÙ Ø§ ÙØ¦Ø§Ø«ÙÙØ§Ù ØØ©ÙØ¨Ø§ÙÙÙ Ø§ÙÙ ÙØ¹ØªÙØ§Ù Ù ÙÙØ¹ØªÙØ§ Ø©ÙÙÙ Ø¹ Ø¡Ø§ÙØ«Ø£ Ø³Ø§Ù ÙØØ§Ù ØØ©Ø¯Ø¦Ø§ÙÙØ§Ù ØØ¨ÙØ§Ø·ÙØ§ Ø¹ØªÙ ØªÙØ§ ÙØ¹Ø¬Ù Ù ÙØ§ÙØªÙØ§ Ø±ÙÙØ·Øª ÙØ¬Ø£ ÙÙ ØªØ§ÙÙÙØª Ø©Ø¯Ø¹